Convolutional Neural Networks for Real-Time Intrusion Detection in Network Security Architectures - Sridhar Sriharsha Rachakonda ,Ramesh Lakshmikanth, (Journal of Computational Analysis and Applications (JoCAAA), 2026)
Intrusion detection remains one of the mostcritical challenges in safeguarding modern network infrastructures, particularly as cyberattacks continue to evolvein scale and sophistication. Conventional approaches